Implications of carbohydrate sources and rate of body weight gain on puberty in ewe lambs in tropical climate conditions - Ferreira, Evandro Maia; Castro Ferraz, Marcos Vinicius de; Biava, Janaina Socoloviski; Assis, Rhaissa Garcia de; Roman Barroso, Jose Paulo; Polizel, Daniel Montanher; Araujo, Leandro Coelho de [UNESP]; Pires, Alexandre Vaz (Springer, 2020)
The objectives were to evaluate the effects of two non-fibrous carbohydrate sources and the rate of body weight gain on puberty status in ewe lambs. Sixty ewe lambs (1/2 Dorper x 1/2 Santa Ines) with an initial body weight of 25.1 +/- 4.1 kg and 102.8 +/- 1.5 days old were distributed in a randomized complete block design with 10 blocks and 3 treatments. The trial lasted 119 days, in which performance was evaluated on days 28, 56, 84, and 119, and puberty status was every week evaluated by progesterone concentration. The treatments were characterized by the inclusion of different carbohydrate sources in the diets in order for ewe lambs to reach different rates of body weight gain: CORN, total diet containing 46% of corn (% DM); PCP, total diet containing 46% of pelleted citrus pulp (% DM); and HAY, total diet containing 80% of coastcross hay (% DM). The CORN- and PCP-based diets were formulated for an average daily gain (ADG) of 0.200 kg/day and a HAY-based diet for an ADG of 0.100 kg/day. There was an interaction between treatments and experimental periods for dry matter intake (DMI) (P < 0.01), in which lambs in the CORN treatment presented DMI similar to PCP in the first and second periods, but lambs from the PCP treatment presented lower DMI than the CORN treatment in subsequent periods. In all periods, the body weight, average daily gain, and feed efficiency of CORN lambs were similar to PCP lambs, but higher thanHAY lambs. The age at puberty was not affected by treatments; however, lambs fed with non-fibrous carbohydrate sources reached puberty heavier (P < 0.0001) than lambs from the HAY treatment. Despite the high increase in body weight for lambs fed with non-fibrous carbohydrate sources, it did not affect the age of puberty.
Keywords: Sheep; Breeding; Pelleted citrus pulp; Corn; Hay